Untersuchungen zur kommerziellen Lexikographie der deutschen Gegenwartssprache. Band 1. (Lexicographica. Series Maior, 2003)
In commercial lexicography, the aspect of dictionaries as saleable commodities determines the laws governing lexicographic action. Accordingly, the planning and ordering of dictionaries is dictated by the laws of the marketplace and those providing the necessary funds can assert their influence on the content of dictionaries. The present collection informs its readers on the degree to which a legitimate concern for profitability has been appropriately reconciled with culturally responsible activity. An essential factor in this regard is the extent to which academic standards and the insights gleaned from recent dictionary research are taken account of in the practicalities of commercial lexicography.